EQUIPMENT ANAEROBIC DIGESTION OF SEWAGE SLUDGE FROM METOYUOTRYMANNYA AND BIOGAS UTILIZATION IN COMMUNAL SEWAGE TREATMENT FACILITIES - , С. Б., К. Б. (Municipal economy of cities (Technical science), 2013)
The analysis of the main factors, parameters and characteristics of equipment stores anaerobic digestion of sewage sludge that affect the stability of the formation of biogas